2021
DOI: 10.21203/rs.3.rs-547438/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Injection of Cerium Oxide Nanoparticles To Treat Spinal Cord Injury In Rats

Abstract: Introduction: The present study, investigated the local injection of cerium oxide nanoparticles (CeONPs) into Spinal cord injury (SCI) lesions in rats, and the effect on motor performance and neuropathic pain, together with biochemical markers.Methods: 36 adult male Wistar rats were divided into 4 groups: control group (healthy animals); sham group (laminectomy); SCI group (laminectomy+SCI induction); treatment group (laminectomy + SCI induction + intrathecal injection of 10 µL of CeONPs (1000 µg/mL) immediate… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…In the motor function of the left paw, it was observed that the Scaffold alone could not improve movement, but the Scaffold-CeO 2 significantly improved the left paw movement compared to the SCI and Scaffold groups, although this improvement did not reach the level of the control group. This result is consistent with the results of other studies that showed injection of cerium oxide nanoparticles has helped to improve motor function after spinal cord injury [53,54].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the motor function of the left paw, it was observed that the Scaffold alone could not improve movement, but the Scaffold-CeO 2 significantly improved the left paw movement compared to the SCI and Scaffold groups, although this improvement did not reach the level of the control group. This result is consistent with the results of other studies that showed injection of cerium oxide nanoparticles has helped to improve motor function after spinal cord injury [53,54].…”
Section: Discussionsupporting
confidence: 93%
“…Kim et al also showed that CeONPs had an antioxidant effect in spinal cord injury and subsequently improved the functional recovery in rats after mild traumatic brain injury [53]. In last work our team also demonstrated the healing effect of soluble CeONPs on neuronal regeneration after SCI [54] but at the present study, the release of nanoparticles was continuously from the fabricated scaffold, and the novelty of this study lies in this issue. In the present study, we investigated the effect of a gelatinous poly (ε-caprolactone) scaffold containing CeONPs (Scaffold-CeO 2) implanted at the site of injury on nerve cell growth and pain relief in a SCI animal model.…”
mentioning
confidence: 60%
See 1 more Smart Citation
“…Although all people experience pain, many patients suffered chronic pain, which is so excruciating and affects the patient's quality of life [1][2][3]. Various chemicals [4] and natural substances [5,6] and new treatment methods such as photobiomodulation therapy [7,8] have shown analgesic effects but their administration is not approved.…”
Section: Introductionmentioning
confidence: 99%
“…[3,4]. Traumatic SCI often lead to devastating loss of sensory and motor function, and despite therapeutic methods which have shown positive results in the research phase [5][6][7][8][9][10] so far there is no drug treatments that can restore function consistently in affected patients Although there is some spontaneous regenerative responses that occurs following SCI, this is often insufficient for significant improvement [11]. Several factors, including inappropriate immune responses, glial scar development, and lack of adequate neurotrophic support after SCI may be the cause of this lack of regenerative ability [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%